Life Course and Gender: Unpacking Women’s Thoughts About Access to the Superintendency - Calderone, Shannon M.; McDonald, Teena; Hill, Glenys; Derrington, Mary Lynne (Frontiers in Education, 2020)
Abstract The current study utilizes feminist life course theory to examine the perspectives of women who have aspired or have entered into the superintendency in the United States. Life course theory suggests that our choices about careers are often founded upon “role histories” - near instantaneous responses to the social cues of our external world. Consequently, it offers opportunity to understand how patterns of socialization may impact real-life decisions over career possibilities (and impossibilities) and the historical conditions in which career decisions are made. Using survey responses from current and aspiring female superintendents (n=133), we engaged in descriptive statistical analyses. These findings were further contextualized through the four principles of life course theory, historical time and place, timing in lives, linked lives, and human agency. Our findings indicate women’s perspectives on the accessibility of the superintendency have shifted as narratives around women’s executive leadership roles have also changed. Importantly, the women in this study view accessibility to the superintendency as a largely contingent decision - a strategic, individual-level assessment focusing on the favorability of district work conditions to their success as leaders. Simultaneously, we see where issues of social networking, leadership “tapping”, and district “fit” emerge as normative expectations for accessing leadership roles as well as the preferred conditions upon which such choices are made. This reflects an encouraging perspective shift in which women are focusing less on “feasibility” than on “fit”. . Recommendations for practice are provided.